2021
DOI: 10.3389/fbioe.2021.754113
|View full text |Cite
|
Sign up to set email alerts
|

3D Bioprinted Implants for Cartilage Repair in Intervertebral Discs and Knee Menisci

Abstract: Cartilage defects pose a significant clinical challenge as they can lead to joint pain, swelling and stiffness, which reduces mobility and function thereby significantly affecting the quality of life of patients. More than 250,000 cartilage repair surgeries are performed in the United States every year. The current gold standard is the treatment of focal cartilage defects and bone damage with nonflexible metal or plastic prosthetics. However, these prosthetics are often made from hard and stiff materials that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 176 publications
0
14
0
Order By: Relevance
“…As a personalized and flexible technology, 3D bioprinting has a broad application prospect in repairing IVDs. 125 Depending on the device, printing parameters, and printing time, 3D printing technology can not only print biological materials but also accurately place growth factors or cells. Sun et al 101 developed polydopamine nanospheres loaded with TGF-β3/connective tissue growth factor (CTGF) and mixed them with bone marrow MSCs and hydrogel to design and fabricate IVD scaffolds using a novel 3D printing technique.…”
Section: Molecular Pharmaceutics Pubsacsorg/molecularpharmaceuticsmentioning
confidence: 99%
“…As a personalized and flexible technology, 3D bioprinting has a broad application prospect in repairing IVDs. 125 Depending on the device, printing parameters, and printing time, 3D printing technology can not only print biological materials but also accurately place growth factors or cells. Sun et al 101 developed polydopamine nanospheres loaded with TGF-β3/connective tissue growth factor (CTGF) and mixed them with bone marrow MSCs and hydrogel to design and fabricate IVD scaffolds using a novel 3D printing technique.…”
Section: Molecular Pharmaceutics Pubsacsorg/molecularpharmaceuticsmentioning
confidence: 99%
“…Extensive studies have shown that 3D bioprinting, [2] as a promising method, enables the design of spatially complex tissue structures in vitro and their potential implantation in vivo, providing an alternative approach for treating meniscal injuries. [3][4][5] Both meniscectomy and meniscus repair, as well as the utilization of meniscus allograft, have limitations in fully restoring the biomechanical properties and stability of the knee joint. Overcoming the challenge of reconstructing the structural inhomogeneity and anisotropy of the meniscus is a significant hurdle in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have shown that 3D bioprinting, [ 2 ] as a promising method, enables the design of spatially complex tissue structures in vitro and their potential implantation in vivo, providing an alternative approach for treating meniscal injuries. [ 3–5 ]…”
Section: Introductionmentioning
confidence: 99%
“…Natural materials such as chitin, gelatin, and alginate have also been used to produce hydrogels like chitosan and gelatin methacryloyl (GelMA) that act as scaffolds and promote ECM production ( Guo et al, 2014 ; Li et al, 2017 ; Yang et al, 2020 ). Hydrogels and 3D printed implants to replace the damaged NP have shown potential to restore disc height and reduce pain ( Schmocker et al, 2016 ; Perera et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%